(untitled) (International Journal of Engineering and Computer Science, 2014)
Nowadays video surveillance systems have been developing rapidly. Video surveillance systems detect the target in initial stage and then perform the functions like object classification, its behavioural description & tracking. However there are many problems associated with object detection & tracking, such as illumination changes, fake motion, image noise etc. To overcome such problems, a system based on Particle filter algorithm is proposed in this paper. An attempt has been made to develop effective object detection & tracking system